2021
DOI: 10.21037/tau-20-1250
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of a ceRNA network and patterns of immune infiltration in bladder cancer

Abstract: Background: Bladder cancer (BC) is the ninth most common malignant tumor, accounting for an estimate of 549,000 new BC cases and 200,000 BC-related deaths worldwide in 2018. The prognosis of BC has not substantially improved despite significant advances in the diagnosis and treatment of the disease. Methods:The RNA sequencing (RNA-seq) data and clinical information of BC patients were downloaded from The Cancer Genome Atlas (TCGA) database. The Cell-type Identification By Estimating Relative Subsets Of RNA Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Tumor immune microenvironment plays a key role in the occurrence and development of tumors 22 . Research have released that DSC2 was associated with immune cell infiltration in bladder cancer 23 . Similarly, we also found that DSC2 was strongly associated with most immune cell infiltration, such as Neutrophils, M2 Macrophages, Eosinophils, resting Dendritic cells, CD8 T cells and CD4 memory activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor immune microenvironment plays a key role in the occurrence and development of tumors 22 . Research have released that DSC2 was associated with immune cell infiltration in bladder cancer 23 . Similarly, we also found that DSC2 was strongly associated with most immune cell infiltration, such as Neutrophils, M2 Macrophages, Eosinophils, resting Dendritic cells, CD8 T cells and CD4 memory activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Cibersort analytical tool can be used to calculate the relative content of 22 specific immune cell subtypes in the TME based on machine learning algorithms (9). Based on this approach, several studies have established prognostic models for various types of cancer (10)(11)(12)(13)(14). Cibersortx, an upgraded version of Cibersort, could be applied to establish multi-gene signatures of cell subpopulations based on scRNA-seq data and be used to analyse the relative content of these subpopulations (15).…”
mentioning
confidence: 99%